2017
DOI: 10.1002/14651858.cd001754.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Traditional suburethral sling operations for urinary incontinence in women

Abstract: Analysis 5.10. Comparison 5 Sling versus open abdominal retropubic suspension, Outcome 10 Operative time (minutes). Analysis 5.11. Comparison 5 Sling versus open abdominal retropubic suspension, Outcome 11 Time to catheter removal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 93 publications
1
41
0
1
Order By: Relevance
“…As one of the first procedures described to treat SUI, the modern autologous fascial sling was introduced in the 1940s and adapted into the 20th century . Still recommended as a treatment for SUI today, a recently updated Cochrane review details the efficacy of this procedure compared to the MUS.…”
Section: Mus Compared To Other Continence Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the first procedures described to treat SUI, the modern autologous fascial sling was introduced in the 1940s and adapted into the 20th century . Still recommended as a treatment for SUI today, a recently updated Cochrane review details the efficacy of this procedure compared to the MUS.…”
Section: Mus Compared To Other Continence Proceduresmentioning
confidence: 99%
“…As one of the first procedures described to treat SUI, the modern autologous fascial sling was introduced in the 1940s and adapted into the 20th century . Still recommended as a treatment for SUI today, a recently updated Cochrane review details the efficacy of this procedure compared to the MUS. Twelve trials addressed the comparison and found them to be equally effective in the short term (up to 1 year) (RR, 0.97; 95% CI, 0.78‐1.20) but MUS was found to have the advantage of a shorter operating time, fewer perioperative complications (excluding bladder perforation) and some evidence suggesting less postoperative voiding dysfunction and de novo detrusor overactivity.…”
Section: Mus Compared To Other Continence Proceduresmentioning
confidence: 99%
“…All of the seven randomized or quasi‐randomized trials comparing PVS and colposuspension have been previously reviewed in ICI‐5. The Cochrane Systematic Review was updated in 2017 and no new comparisons between PVS and colposuspension were added . Since ICI‐5, there have been no new comparisons between PVS and MUS and no new comparisons between one type of PVS and another.…”
Section: Traditional Pubovaginal Slings (Pvs)mentioning
confidence: 99%
“…The controversy about the use of MUS has increased the importance of traditional continence operations such as PVS and BC. Robust evidence for comparison of these procedures is lacking . The only one well‐designed, adequately powered RCT (SISTEr) showed a higher cure rate, a higher risk of voiding dysfunction and a lower risk of POP for the autologous fascial sling (AFS) compared with BC .…”
Section: Methodsmentioning
confidence: 99%